The effect of breakfast cereal consumption on adolescents' cognitive performance and mood - Defeyter, Margaret A.; Russo, Riccardo (Frontiers in Human Neuroscience, 2013)
The aim of the current study was to investigate the effect of breakfast consumption on cognitive performance and mood in adolescents, and any interaction that breakfast consumption might have with cognitive load. The rationale for this approach was that the beneficial effects of any intervention with regard to cognitive function may be more readily apparent when more demands are placed on the system. Furthermore, as skipping breakfast is particularly prevalent within this age group, thus, we focused on adolescents who habitually skip breakfast. Cognitive load was modulated by varying the level of difficulty of a series of cognitive tasks tapping memory, attention and executive functions. Mood measured with Bond-Lader scales (1974) as well as measures of thirst, hunger and satiety were recorded at each test session both at baseline and after the completion of each test battery. Forty adolescents (mean age = 14:2) participated in this within-subjects design study. According to treatment, all participants were tested before and after the intake of a low Glycaemic index breakfast (i.e. a 35g portion of AllBran and 125ml semi-skimmed milk) and before and after no breakfast consumption. Assessment time had two levels: 8.00am (baseline) and 10.45am. The orders of cognitive load tasks were counterbalanced. Overall it appeared that following breakfast participants felt more alert, satiated and content. Following breakfast consumption, there was evidence for improved cognitive performance across the school morning compared to breakfast omission in some tasks (e.g. Hard Word Recall, Serial 3’s and Serial 7’s). However, whilst participants performance on the hard version of each cognitive task was significantly poorer compared to the corresponding easy version, there was limited evidence to support the hypothesis that the effect of breakfast was greater in the more demanding versions of the tasks.